Snow persistence grids and snow zone shape files for the western United States - Moore, Cara; Kampf, Stephanie; Stone, Brandon; Richer, Eric (Colorado State University. Libraries, 2012)
This study maps the geographic extent of intermittent and seasonal snow cover in the western United States using thresholds of 2000–2010 average snow persistence derived from moderate resolution imaging spectroradiometer snow cover area data from 1 January to 3 July. Results show seasonal snow covers 13% of the region, and intermittent snow covers 25%. The lower elevation boundaries of intermittent and seasonal snow zones increase from north-west to south-east. Intermittent snow is primarily found where average winter land surface temperatures are above freezing, whereas seasonal snow is primarily where winter temperatures are below freezing. However, temperatures at the boundary between intermittent and seasonal snow exhibit high regional variability, with average winter seasonal snow zone temperatures above freezing in west coast mountain ranges. Snow cover extent at peak accumulation is most variable at the upper elevations of the intermittent snow zone, highlighting the sensitivity of this snow zone boundary to climate conditions.
These files were created by Cara Moore and Brandon Stone under the guidance of Stephanie Kampf at Colorado State University in July, 2012.
Zip file includes ReadMe and data files.
Department of Ecosystem Science and Sustainability
Natural Resource Ecology Laboratory (NREL)
Keywords: seasonal snow; intermittent snow; snow zones; MODIS snow cover; MODIS land surface temperature; western United States